PEMBERDAYAAN MASYARAKAT MELALUI POKDARWIS DAN LITERASI DIGITAL UNTUK PENGEMBANGAN WISATA JORONG KUOK KABUPATEN AGAM - Yudhi Andoni; Alex Darmawan; Yenny Narny (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Community-based tourism development offers a sustainable approach to social and economic transformation, particularly in rural areas rich in cultural and historical potential. However, many communities, such as Jorong Kuok III Koto in Nagari Matua Mudiak, face challenges such as limited awareness of local potential and insufficient technical skills to manage and utilize these resources. Addressing this issue, the Community Service Program (PKM) titled "Assisting Nagari Development" aimed to empower the local community through the integration of cultural heritage preservation and digital technology. This program focused on enhancing the community’s capacity to document local history, manage tourism organizations, and utilize digital platforms for promotion. The program was conducted in four stages: identification of local potential through interviews with elderly residents, training in oral history documentation and digital tools, the establishment of a community tourism group (Pokdarwis), and dissemination activities, including a tourism pilot project and cultural festival. Results revealed increased community awareness of the socio-economic value of cultural heritage, enhanced digital skills among youth, and the successful formation of Pokdarwis to manage local tourism initiatives. Challenges included limited time and resources of community members and administrative delays, which were mitigated through flexible planning and remote training. This program demonstrated the transformative potential of participatory approaches in fostering community-led tourism development. It provided a replicable model for integrating cultural preservation and technology to empower rural communities and promote sustainable tourism. Future efforts will focus on scaling up these initiatives for broader impact.